The Role of Astrocytes in Neuroprotection after Brain Stroke: Potential in Cell Therapy - Becerra-Calixto, Andrea; Cardona-Gómez, Gloria P. (Frontiers in Molecular Neuroscience, 2017)
Astrocytes are commonly involved in negative responses through their hyperreactivity and glial scar formation in excitotoxic and/or mechanic injuries. But, astrocytes are also specialized glial cells of the nervous system that perform multiple homeostatic functions for the survival and maintenance of the neurovascular unit. Astrocytes have neuroprotective, angiogenic, immunomodulatory, neurogenic, and antioxidant properties and modulate synaptic function. This makes them excellent candidates as a source of neuroprotection and neurorestoration in tissues affected by ischemia/reperfusion, when some of their deregulated genes can be controlled. Therefore, this review analyzes pro-survival responses of astrocytes that would allow their use in cell therapy strategies.